Analisis Dasar Pertimbangan Hakim Terhadap Putusan Praperadilan dalam Perkara Error In Persona (Studi Putusan Nomor 1/Pid.Pra/2019/PN Kbu) - Putri, Abelia Zahara; Rumelawanto, Fajar Putra Prastina (Jurnal Locus Penelitian dan Pengabdian, 2025)
The predicate of the Unitary State of the Republic of Indonesia as a state of law, means that all behavior of society must be regulated and implemented with strict sanctions and anyone who violates the law will be held accountable for their actions if proven to have committed a mistake. However, the suspect or defendant is a legal subject who has the right to obtain legal protection guarantees, one of which is through pretrial legal efforts. This study aims to determine the mechanism for implementing the pretrial process and to analyze the basis for the judge's considerations in granting pretrial regarding compensation for victims of mistaken arrest or error in persona, as stated in Article 9 paragraph (2) of Government Regulation Number 92 of 2015 in Decision Number 1 / Pid.Pra / 2019 / PN Kbu. This study is a normative legal research that examines the judge's considerations based on Decision Number 1 / Pid.Pra / 2019 / PN Kbu with the provisions contained in the Criminal Procedure Code. The research source collection technique used is literature study, while the research analysis uses deductive syllogism by collecting research sources to understand related norms. Based on the research results, it can be concluded that the judge's considerations in granting the pretrial motion regarding the pretrial decision in this error in persona case are in accordance with the provisions of the Criminal Procedure Code.